Central African Economic and Monetary Community (CEMAC) : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper focuses on the need of improving liquidity management and the operational framework of monetary policy in Central African Economic and Monetary Community (CEMAC). Disconnected policy and lending rates reflect the ineffective interest rate channel of monetary policy transmission while the shallow domestic banking system and the underdeveloped financial markets induce weaknesses of both the credit and asset price channels. In the absence of an efficient interest rate channel, liquidity plays an important role in the conduct of monetary policy. The CEMAC economy is vulnerable to external shocks and its banking system potentially exposed to liquidity shocks. Successful monetary policy implementation requires a set of appropriate instruments to cope with various liquidity shocks. The origins of the surplus liquidity should be well known upfront and addressed with a suitable combination of measures, including foreign exchange, fiscal and financial system development policies. The paper recommends that the Bank of Central African States should investigate all the means to centralize and analyze relevant information for autonomous factors forecasts, including daily operations of Treasuries and foreign exchange operations from its accounting system, as well as banknotes in circulation.